Peran Penyuluh Pertanian Lapang (PPL) dalam Meningkatkan Kemampuan Petani pada Deteksi Dini Penyakit Patogen pada Tembakau di Kecamatan Sulang Kabupaten Rembang - Dinda Catur Ariyani; Sugihardjo Sugihardjo; Diwi Acita Irawati (Agroekotek View, 2026)
Tobacco is one of the leading plantation commodities in Sulang District, Indonesia, but its productivity and quality are often reduced by pathogen diseases. Improving farmers’ ability to detect these diseases at an early stage is essential for effective disease management. Agricultural Extension Workers (AEWs) play a strategic role in strengthening farmers’ knowledge and skills through extension services and technical assistance. This study aimed to analyze tobacco farmers’ ability to conduct early detection of pathogen diseases, identify the roles of Agricultural Extension Workers, and examine the relationship between the roles of AEWs and farmers’ disease detection ability. A descriptive survey method was employed in Sulang District using purposive site selection. Data were collected from 81 tobacco farmers selected from a population of 423 using the Slovin formula. Questionnaires, interviews, observations, and documentation were used for data collection. Descriptive statistics and Spearman Rank correlation were applied for data analysis. The results indicated that farmers’ ability to detect pathogen diseases was at a moderately good level. The performance of Agricultural Extension Workers was also assessed as moderately good, particularly in their roles as facilitators, innovators, motivators, dynamists, and educators. Spearman Rank correlation analysis revealed that all extension roles had positive and significant relationships with farmers’ early disease detection ability. The educator role showed the strongest correlation (rₛ = 0.669), indicating its substantial contribution to improving farmers’ knowledge and skills. These findings highlight the importance of strengthening agricultural extension services to enhance farmers’ capacity for early disease detection and support sustainable tobacco production